Effectiveness And Stability Analysis Of Embankment Using Lightweight Embankment On Pasuruan - Probolinggo Toll Road Project Section 4, Indonesia - Ritwandanu, Ruri Febri; Wahyudi, Herman; Lastiasih, Yudhi; Mufijar, Hamim (Journal of Infrastructure & Facility Asset Management, 2024)
The Pasuruan-Probolinggo Section 4 Toll Road project which has a length of 12.04 km is dominated by silty clay - clay. In addition to soft soil, there are other problems in the construction of the Pasuruan - Probolinggo Section 4 toll road, namely the limited availability of embankment soil material around the project site and the location of the quarry which is quite far away. In addition, when relying on embankment material from the quarry, the weather factor will play a very important role when the weather is rainy then the activity in the quarry stops, the targeted embankment volume is not met and the progress of work on that day is not achieved. Therefore, there is a need for alternative reinforcement of embankments other than soil embankments from quarries that are safe and light enough. Based on the existing problems, this research will conduct a comparative study of toll road embankment design with 3 different types of materials, namely: Conventional soil embankment compared with lightweight embankment in the form of EPS-Geofoam material and foam mortar material.  This research will use Plaxis 2D program. The results of this research will determine alternative embankment materials that can be applied to soft subgrade so that overall stability and hydrostatic uplift  requirements can be met. This research is expected to be a reference in planning the construction and improvement of the subgrade of the Pasuruan-Probolinggo Section 4 toll road and other toll roads using EPS geofoam embankment and foam mortar